DAMPAK POLA KEMITRAAN MELALUI E-COMMERCE PERTANIAN (Kasus pada Petani Jeruk dengan PT. TaniHub Indonesia di Kabupaten Malang) - Moch. Agus Junaidi; Eka Putri Maghdahfanti (Universitas Islam Kadiri, 2020)
The number of internet users in Indonesia continues to increase every year. PT. TaniHub Indonesia (TaniHub) is one of the results of the existence of the development of the internet, especially e-commerce in agriculture. In Addition, the number of Baby Java orange production has increased significantly. However, the production value of oranges is not accompanied by a good marketing system, which has impact to the marketing efficiency. The large amount of orange production in Malang District is also become an opportunity for TaniHub to develop e-commerce partnership program with the orange’s farmers. This study aims to identify impacts of e-commerce partnership program between orange’s farmers and TaniHub. Taking a case in Malang, District, semi-structured interview was applied in this study. The e-commerce partnership program has a good impact on farmers’ behaviors, especially access to information and technology (IT). However, farmers’ motivation in this program become a challenge for the sustainability of the e-commerce partnership program.